STUDENTS' LEARNING PROCESS TOWARDS HISTORY SUBJECT AT SENIOR HIGH SCHOOL 1 TIBAWA - Adam, Regita Cahyani; Mondong, Tonny Iskandar; Mohamad, Sutrisno (CV. Fahr Publishing, 2024)
SMA Negeri 1 Tibawa is one of the educational institutions in Gorontalo Regency that offers History as a subject. However, students often feel bored with the material presented, as the narratives of the past are considered less engaging. This condition can impact the learning process, particularly due to students' low motivation to learn. This study focuses on two main aspects: 1) What is the level of students' motivation in learning History at SMA Negeri 1 Tibawa?; 2) What factors influence students' motivation in learning History at this school? The research employed a qualitative approach with a narrative method, and the subjects were purposively selected. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out using the results of students' tests or evaluations. The findings of the study revealed several key points: 1) In the initial sessions, students’ motivation to learn History varied, with some showing low interest and others displaying higher enthusiasm; 2) Students' extrinsic motivation increased through encouragement from teachers, both in the form of verbal support and rewards. Other supporting factors included the availability of facilities, diverse teaching methods, and social interactions with peers, which helped reduce boredom; 3) The implementation of a reward and punishment system proved effective in increasing students' interest in learning. Those who were initially less enthusiastic became more motivated by rewards, while diligent students were further driven to improve their performance to gain recognition from teachers and peers. This appreciation also contributed to students' confidence in completing assignments, enabling teachers to manage the classroom more effectively.